Concordant low and discordant fractional flow reserve and instantaneous wave-free ratio measurements are associated with reduced myocardial perfusion. (3rd October 2022) - De Winter, R W; Van Diemen, P A; Schumacher, S P; Jukema, R A; Somsen, Y B O; Bom, M J; Everaars, H; Van Rossum, A C; Verouden, N J; Raijmakers, P G; Nap, A; Driessen, R S; et al.
Abstract: Background: In patients undergoing invasive coronary angiography with functional lesion assessment, both fractional flow reserve (FFR) and instantaneous wave-free ratio (iFR) measurements can be used to guide coronary revascularization decision-making. The hemodynamic significance of lesions with discordant FFR and iFR measurements is debated. Purpose: This study compared quantitative myocardial perfusion indices as assessed by [15O]H2O positron emission tomography (PET) perfusion imaging in vessels with concordant high, discordant and concordant low FFR/iFR measurements Methods: This post-hoc analysis of the PACIFIC I and II studies included 198 patients suspected of obstructive coronary artery disease who had undergone [15O]H2O PET imaging and subsequent FFR/iFR interrogation in 468 vessels. Resting myocardial blood flow (MBF), hyperemic MBF and coronary flow reserve (CFR) were compared between 4 vessel subgroups: FFR+/iFR+ (n=79), FFR−/iFR+ (n=22), FFR+/iFR− (n=22) and FFR−/iFR− (n=345). Results: Discordant FFR/iFR indices were found in 44 (9%) vessels. Hyperemic MBF was significantly lower for vessels with FFR+/iFR+ (2.09±0.67 mL min –1 g –1 ), FFR−/iFR+ (2.41±0.80 mL min –1 g –1 ) and FFR+/iFR− (2.40±0.69 mL min –1 g –1 ) compared to FFR−/iFR− vessels (2.91±0.84 mL min –1 g –1 ) (p<0.01, p=0.03 and p<0.01, respectively). Hyperemic MBF did not differ between vessels with FFR+/iFR+ compared to FFR−/iFR+ (p=0.38) and FFR+/iFR− (p=0.35) vessels. In addition, resting MBF was lower and CFR did not differ in the FFR+/iFR− versus the FFR−/iFR− group (resting MBF: 0.80±0.16 mL min –1 g –1 vs. 0.90±0.24 mL min –1 g –1, p=0.03 and CFR: 3.05±0.84 vs. 3.35±1.07, p=0.56). Finally, CFR was similar in FFR+/iFR+ and FFR−/iFR+ vessels (2.37±0.76 vs. 2.64±0.84, p=0.92). Conclusions: We found lower baseline flow and similar flow reserve in FFR+/iFR− compared to FFR−/iFR− vessels. Importantly, [15O]H2O PET imaging demonstrated reduced hyperemic MBF in vessels with concordant low and discordant FFR and iFR measurements. Funding Acknowledgement: Type of funding sources: None.